The truth as told by Mason Buttle - Connor, Leslie (Katherine Tegen Books, 2020)
Mason Buttle is the biggest, sweatiest kid in his grade and can barely read or write. Fifteen months ago, Mason's best friend, Benny, was found dead in the Buttle family orchard and as the investigation drags on, Mason can't understand why the police won't believe his story about what happened. When Mason and his new friend Calvin make an underground club space in order to escape the neighborhood bullies, Mason finds himself in even more trouble and becomes desperate to figure out what happened to Calvin and Benny.